1997
DOI: 10.1038/sj.bmt.1700767
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell markers in bone marrow transplant recipients with and without acute graft-versus-host disease

Abstract: Summary:and capillary leak syndrome. Microangiopathy, a characteristic form of EC damage associated with severity of GVHD in recipients of allogeneic bone marrow transplants, has To investigate endothelial cell alterations in BMT recipients developing acute graft-versus-host disease been described earlier by our group 1,2 suggesting that not only the epithelium but also EC may be affected in the (aGVHD) we determined levels of the endothelial cell markers von Willebrand factor (VWF) and thrombomcourse of aGVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 2 publications
2
45
2
Order By: Relevance
“…24 In addition, conditioning treatment may significantly affect the complement system and coagulation parameters, thereby provoking severe acute complications such as VOD and capillary leakage syndrome. 22,25,27,28 Our analysis of the O-PRISM score demonstrates the early prognostic impact of the O-PRISM score and thus provides evidence that these experimental observations may be of significant clinical relevance. In addition, the O-PRISM score may help to identify a group of high-risk patients early who may benefit from alternative supportive strategies.…”
Section: Discussionmentioning
confidence: 93%
“…24 In addition, conditioning treatment may significantly affect the complement system and coagulation parameters, thereby provoking severe acute complications such as VOD and capillary leakage syndrome. 22,25,27,28 Our analysis of the O-PRISM score demonstrates the early prognostic impact of the O-PRISM score and thus provides evidence that these experimental observations may be of significant clinical relevance. In addition, the O-PRISM score may help to identify a group of high-risk patients early who may benefit from alternative supportive strategies.…”
Section: Discussionmentioning
confidence: 93%
“…Zeigler et al 20 observed that VWF and TM were increased in all patients with TAM after HSCT. Salat et al 21 evidenced that VWF and TM rose significantly after conditioning in all patients. At the time of engraftment or at the onset of GVHD, VWF and TM levels were significantly increased with respect to the baseline, especially in patients with acute GVHD grades II-IV, suggesting that ECs could be injured.…”
Section: Soluble Markers and Adhesion Moleculesmentioning
confidence: 99%
“…TMA, a characteristic form of endothelial cell damage, has been associated with acute GVHD, cytotoxic drugs, irradiation, and viral infections such as cytomegalovirus and human herpesvirus-6 in patients with BMT. [1][2][3][4][5] It is well known that damage or activation of vascular endothelial cells, mediated by cytokines such as interleukin-1 or tumor necrosis factor-␣, induces expression of vascular adhesion molecules, ie intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1), and E-selectin, on their cell surface. 6 This process appears to be important in the recruitment of leukocytes to the site of inflammation.…”
mentioning
confidence: 99%